2018
DOI: 10.21278/tof.41402
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Corrosion Behaviour of 316l Stainless Steel Honeycomb Cellular Cores Manufactured by Selective Laser Melting

Abstract: SummarySelective laser technology is an additive technology that can allow for the manufacture of cellular structures using different types of metallic powder with complex applications in industries such as aerospace, automotive and medical implant industries. This paper presents the effect of climate and mechanical stresses on some honeycomb cellular cores, used in sandwich structures made of 316L stainless steel powder by applying the selective laser melting technology. The honeycomb cellular cores have unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…It was reported by Brown et al (2016) that thin SLM manufactured 304 L samples of 0.25 mm thickness, exhibited reduced strength due to surface roughness and increased porosity. In another experimental study (Zaharia et al , 2017), hexagonal honeycombs were manufactured using SLM of 316 L and tested by flatwise and edgewise (L-direction only) compression. Accelerated corrosion behavior was also investigated for the manufactured honeycombs of 14 mm cell size and 1.5 mm wall thickness.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported by Brown et al (2016) that thin SLM manufactured 304 L samples of 0.25 mm thickness, exhibited reduced strength due to surface roughness and increased porosity. In another experimental study (Zaharia et al , 2017), hexagonal honeycombs were manufactured using SLM of 316 L and tested by flatwise and edgewise (L-direction only) compression. Accelerated corrosion behavior was also investigated for the manufactured honeycombs of 14 mm cell size and 1.5 mm wall thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The authors revealed that more closely-packed crystal planes (111) and reduced grain sizes of the SLM samples led to improved corrosion behavior. Zaharia et al examined the corrosion behavior of 316L honeycomb cores by measuring actual weight loss without the electrochemical corrosion tests [18]. They adopted an accelerated experiment where 5% and 10% concentrated NaCl solutions were used, which allowed them to infer the corrosion behavior for five and a half years from a 10-day test.…”
Section: Corrosion Behaviors Of Slm 316l Ss Corrosion Behaviors Of Slmentioning
confidence: 99%
“…They adopted an accelerated experiment where 5% and 10% concentrated NaCl solutions were used, which allowed them to infer the corrosion behavior for five and a half years from a 10-day test. Chao et al studied the effects of the MnS content and the presence of the Cr Zaharia et al examined the corrosion behavior of 316L honeycomb cores by measuring actual weight loss without the electrochemical corrosion tests [18]. They adopted an accelerated experiment where 5% and 10% concentrated NaCl solutions were used, which allowed them to infer the corrosion behavior for five and a half years from a 10-day test.…”
Section: Corrosion Behaviors Of Slm 316l Ss Corrosion Behaviors Of Slmentioning
confidence: 99%
See 1 more Smart Citation
“…corrosion damage, can be characterized as a spontaneous heterogeneous chemical process in which the reactants are the environment (one or more of its components) and the structural material. Depending on the conditions of the processes, the products of the mentioned mechanisms also differ and may be of solid, gaseous or dissolved character [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%